Relationships between alexithymia and Machiavellian personality beliefs among university students. Issue 3 (27th May 2017) - Sheikhi, Siamak; Issazadegan, Ali; Norozy, Merseda; Saboory, Ehsan
ABSTRACT: The present study considered the relationships between alexithymia and Machiavellian personality beliefs among university students. Two hundred and thirteen students (95 women and 118 men) studying Master's degrees in psychology, education, law, political sciences, and social sciences at the University of Tehran were randomly chosen using multi-stage clustering sampling and screening. Participants completed the Kiddie Mach scale and Toronto Alexithymia scale (Persian version). Data were analysed by Pearson's correlation coefficient and multivariate regression. Results revealed a significant correlation between alexithymia and Machiavellian views. According to these findings, students with Machiavellian beliefs seemed to run into difficulty with the identification and description of others' emotions.